Chemical structure - biological activity relationships quantitative approaches : proceedings of the 3rd Congress of the Hungarian Pharmacological Society, Budapest, 1979 - Darvas, F. (Advances in pharmacological research and practice ;, 1980)
Chemical Structure-Biological Activity Relationships: Quantitative Approaches, Volume III, documents the proceedings of the 3rd Congress of the Hungarian Pharmacological Society held in Budapest, 1979. This volume focuses on the methodological aspects of QSAR. It also aims to inform the reader about the QSAR research conducted in East-European countries. This volume contains 38 presentations organized into six sections. Several lecturers deal with """"real prediction"""" cases, i.e. activity estimation prior to the synthesis of the compounds. A particularly abundant section is devoted to the q